Решить уравнение нужно -2x(1-x)+3(x-4)=-x(x+2)-6x

katalkina17 katalkina17    1   23.09.2019 17:30    1

Ответы
Евгений006 Евгений006  08.10.2020 12:53
 - 2x(1-x)  + 3(x-4) = -x(x+2)  - 6x
-2x + 2x²  + 3x  - 12  =  -x²  - 2x  - 6x
2x² +x  - 12  =  -x²  - 8x
2x²  + x  - 12  +x²  + 8x  = 0
3x²  + 9x  - 12  = 0
3(x² + 3x - 4) = 0         |÷3
x²  + 3x - 4 = 0
a = 1 ;  b = 3 ; с = - 4
через дискриминант [ D = b²  - 4ac ] :
D =  3² - 4*1*(-4) = 9 + 16  = 25  = 5²
D >  0  -  два корня уравнения  [  х₁,₂ = (-b ⁻₊√D) /2a  ]
x₁ =  (- 3 - 5)/(2*1) = - 8/2  = - 4
x₂ =  ( - 3 +5)/(2*1) = 2/2  = 1

ответ :  х₁ =  - 4 ;  х₂ = 1 .
Решить уравнение нужно -2x(1-x)+3(x-4)=-x(x+2)-6x
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра